White Matter Integrity in Genetic High-Risk Individuals and First-Episode Schizophrenia Patients: Similarities and Disassociations. - Zhou, Yifang; Liu, Jie; Driesen, Naomi; Womer, Fay; Chen, Kaiyuan; Wang, Ye; Jiang, Xiaowei; Zhou, Qian; Bai, Chuan; Wang, Dahai; Tang, Yanqing; Wang, Fei (BioMed Research International, 2017)
White matter (WM) neuroimaging studies have shown varied findings at different stages of schizophrenia (SZ). Understanding these variations may elucidate distinct markers of genetic vulnerability and conversion to psychosis. To examine the similarities and differences in WM connectivity between those at-risk for and in early stages of SZ, a cross-sectional diffusion tensor imaging study of 48 individuals diagnosed with first-episode SZ (FE-SZ), 37 nonpsychotic individuals at a high genetic risk of SZ (GHR-SZ), and 67 healthy controls (HC) was conducted. Decreased fractional anisotropy (FA) in the corpus callosum (CC), anterior cingulum (AC), and uncinate fasciculus (UF) was observed in both the GHR-SZ and FE-SZ groups, while decreased FAs in the superior longitudinal fasciculus (SLF) and the fornix were only seen in the FE-SZ participants. Additionally, both GHR-SZ and FE-SZ showed worse executive performance than HC. The left SLF III FA was significantly positively correlated with hallucinations, and right SLF II was positively correlated with thought disorder. The presence of shared WM deficits in both FE-SZ and GHR-SZ individuals may reflect the genetic liability to SZ, while the disparate FA changes in the FE-SZ group may represent symptom-generating circuitry that mediates perceptual and cognitive disturbances of SZ and ultimately culminates in the onset of psychotic episodes.